2022
DOI: 10.1002/ntls.20220028
|View full text |Cite
|
Sign up to set email alerts
|

Rational design for high bioorthogonal fluorogenicity of tetrazine‐encoded green fluorescent proteins

Abstract: The development of bioorthogonal fluorogenic probes constitutes a vital force to advance life sciences. Tetrazine‐encoded green fluorescent proteins (GFPs) show high bioorthogonal reaction rate and genetic encodability but suffer from low fluorogenicity. Here, we unveil the real‐time fluorescence mechanisms by investigating two site‐specific tetrazine‐modified superfolder GFPs via ultrafast spectroscopy and theoretical calculations. Förster resonance energy transfer is quantitatively modeled and revealed to go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…34−37 A test expression with sfGFP yielded a fulllength protein as hoped (Figure 1C), but we suspected something was not correct as the protein was green, whereas reactive Tet-containing sfGFP 150 as derived from the DH10B cells was orange (Figure S1) due to quenching of the GFP fluorophore by the encoding of oxidized Tet ncAA. 38 Additionally, a gel mobility shift assay testing the protein's ability to react with an sTCO-PEG 5000 polymer confirmed that only a small fraction of the protein was reactive (Figure 1C). This result was unexpected and led to us evaluating the most plausible explanations for unreactive proteins.…”
Section: ■ Results and Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…34−37 A test expression with sfGFP yielded a fulllength protein as hoped (Figure 1C), but we suspected something was not correct as the protein was green, whereas reactive Tet-containing sfGFP 150 as derived from the DH10B cells was orange (Figure S1) due to quenching of the GFP fluorophore by the encoding of oxidized Tet ncAA. 38 Additionally, a gel mobility shift assay testing the protein's ability to react with an sTCO-PEG 5000 polymer confirmed that only a small fraction of the protein was reactive (Figure 1C). This result was unexpected and led to us evaluating the most plausible explanations for unreactive proteins.…”
Section: ■ Results and Discussionmentioning
confidence: 88%
“…Surprisingly, the majority of expressed protein was prematurely truncated (Figure B), consistent with RF1 outcompeting the suppression of UAG sites by aminoacylated Tet2-tRNA. To address this, we tested expression in a BL21­(DE3)-derived “truncation-free” RF1-knockout cell line, B95­(DE3) Δ A Δ fabR (subsequently referred to here as B95), which has shown robust growth and high GCE yields compared to other RF1-knockout strains. In our hands, B95 has demonstrated robust ncAA encoding under a variety of expression conditions, so we chose it from among the various release-factor-deficient cell lines and cell-free expression systems that all have been able to minimize truncation and improve full-length protein production by increasing UAG readthrough. A test expression with sfGFP yielded a full-length protein as hoped (Figure C), but we suspected something was not correct as the protein was green, whereas reactive Tet-containing sfGFP 150 as derived from the DH10B cells was orange (Figure S1) due to quenching of the GFP fluorophore by the encoding of oxidized Tet ncAA . Additionally, a gel mobility shift assay testing the protein’s ability to react with an sTCO-PEG 5000 polymer confirmed that only a small fraction of the protein was reactive (Figure C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, second-order rate constants (k 2 ) were determined for probes A, B, and C. Previous reports have shown that tetrazines have a unique ability to act as fluorescence quenchers when bound to fluorophores, 62 and as such, GFP fluorescence is quenched when bound to tetrazine. 63,64 Therefore, we predicted that thiomethyltetrazines can quench the fluorescence of GFP-SH when S N Ar chemistry has taken place on cysteine. Furthermore, we can determine k obs by monitoring the decrease in GFP-SH fluorescence over time at different tetrazine concentrations to calculate the biomolecular rate constant (k 2 ) of thiomethyltetrazine labeling on a purified protein.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Next, second-order rate constants (k2) were determined for probes A, B, and C. Previous reports have shown that tetrazines have a unique ability to act as fluorescence quenchers when bound to fluorophores, 62 and as such, GFP fluorescence is quenched when bound to tetrazine. 63,64 Therefore, we predicted that thiomethyltetrazines can quench the fluorescence of GFP-SH when SNAr chemistry has taken place on cysteine. Furthermore, we can determine kobs by monitoring the decrease in GFP-SH fluorescence over time at different tetrazine concentrations to calculate the biomolecular rate constant (k2) of thiomethyltetrazine labeling on a purified protein.…”
Section: Confirming Thiomethyltetrazine Labeling By In Vitro Protein ...mentioning
confidence: 99%